Neo-Nazis in Toronto: The Allan Gardens Riot - Bialystok, Franklin (Canadian Jewish Studies / Études juives canadiennes, 1997)
In the early 1960s, after fifteen years of relative quietude, Canadian Jews once again came under attack by antisemites. Unlike the interwar years, when antisemitism leached down from some politicians and bureaucrats to society in general, this new strain was propagated by a tiny group of self-styled neo- Nazis. It was most virulent in Toronto. The Jewish community there was divided over how to respond. Traditional leaders stressed law and order, while others, led by a few militant survivors, demanded exposure and confrontation. Matters reached a head with a riot that erupted in Allan Gardens when the leader of the neo-Nazis attempted to hold a rally. In the ensuing weeks, the gap in the community widened. Consequently, as part of the healing process, survivors were grudgingly accepted into corridors of power in the Jewish community. For this reason, the riot was the seminal event in the post-war history of the community.